Alliance TESO (2015)
The third version of research hotbeds of EAFITChildren's University and the TESO Digital Plan (between July and October), brought together a hundred children and young people from eighteen educational institutions in Itagí. An opportunity to get closer to problems that have to do with science, social relations, environment and technology.